2005
DOI: 10.1002/jctb.1314
|View full text |Cite
|
Sign up to set email alerts
|

Removal of tannins and polyhydroxy phenols by electro‐chemical techniques

Abstract: The removal of tannins and their basic molecules such as catechol, pyrogallol, phloroglucinol and resorcinol was studied by electro-flotation and electro-oxidation techniques. Iron rods and triple oxide (TaO 2 /RuO 2 /IrO 2 ) coated titanium rods were used as electrodes for electro-flotation and electrooxidation respectively. Interaction of tannins and polyhydroxy phenols with iron oxy-hydroxide formed by anodic dissolution of iron was studied by UV-Visible, FT-IR and zeta-potential measurements. GC-MS was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 32 publications
(28 reference statements)
0
26
1
Order By: Relevance
“…It was also observed that the chlorinated E2 compound was not degraded until the electrolysis time 180 min. Earlier studies have shown that the electro generation of chlorine-based oxidants such as ClO − and Cl 2 , can play active role in oxidation process of the organics [28][29][30]. Nevertheless, no such degradation was observed in the case of chlorinated E2 compound.…”
Section: Effect Of Supporting Electrolytesmentioning
confidence: 81%
“…It was also observed that the chlorinated E2 compound was not degraded until the electrolysis time 180 min. Earlier studies have shown that the electro generation of chlorine-based oxidants such as ClO − and Cl 2 , can play active role in oxidation process of the organics [28][29][30]. Nevertheless, no such degradation was observed in the case of chlorinated E2 compound.…”
Section: Effect Of Supporting Electrolytesmentioning
confidence: 81%
“…With respect to the gallate compounds, the Initial spectra presented a peak at 275 ± 1 nm, characteristic of phenol groups and common for this family of compounds (Berden and Meerts, 1996;Murugananthan et al, 2005). After the addition of laccase, a new shoulder appeared at the range of 240-260 nm, whereas the initial peak was overlapped by absorbances from reaction products (data shown in Appendix A).…”
Section: Part 1: Screening Of Reactantsmentioning
confidence: 87%
“…[44][45][46][47][48][49][50][51] In a typical run, birch sawdust (1.0 g) and methanol (10 mL) were placed in a 50 mL Teon-lined autoclave reactor. The mixture was stirred for 30 min before sealing.…”
Section: Measurement Of Lignin Solubility In Various Solventsmentioning
confidence: 99%